RNF213 Rare Variants in Slovakian and Czech Moyamoya Disease Patients - Kobayashi, Hatasu; Brozman, Miroslav; Kyselová, Kateřina; Viszlayová, Daša; Morimoto, Takaaki; Roubec, Martin; Školoudík, David; Petrovičová, Andrea; Juskanič, Dominik; Strauss, Jozef; Halaj, Marián; Kurray, Peter; et al. (PloS one, 2016)
RNF213/Mysterin has been identified as a susceptibility gene for moyamoya disease, a cerebrovascular disease characterized by occlusive lesions in the circle of Willis. The p.R4810K (rs112735431) variant is a founder polymorphism that is strongly associated with moyamoya disease in East Asia. Many non-p.R4810K rare variants of RNF213 have been identified in white moyamoya disease patients, although the ethnic mutations have not been investigated in this population. In the present study, we screened for RNF213 variants in 19 Slovakian and Czech moyamoya disease patients. A total of 69 RNF213 coding exons were directly sequenced in 18 probands and one relative who suffered from moyamoya disease in Slovakia and the Czech Republic. We previously reported one proband harboring RNF213 p.D4013N. Results from the present study identified four rare variants other than p.D4013N (p.R4019C, p.E4042K, p.V4146A, and p.W4677L) in four of the patients. P.V4146A was determined to be a novel de novo mutation, and p.R4019C and p.E4042K were identified as double mutations inherited on the same allele. P.W4677L, found in two moyamoya disease patients and an unaffected subject in the same pedigree, was a rare single nucleotide polymorphism. Functional analysis showed that RNF213 p.D4013N, p.R4019C and p.V4146A-transfected human umbilical vein endothelial cells displayed significant lowered migration, and RNF213 p.V4146A significantly reduced tube formation, indicating that these are disease-causing mutations. Results from the present study identified RNF213 rare variants in 22.2% (4/18 probands) of Slovakian and Czech moyamoya disease patients, confirming that RNF213 may also be a major causative gene in a relative large population of white patients.